Dampak Pandemi COVID-19 Terhadap Pendapatan Pedagang Kaki Lima pada Car Free Day Kota Banjarbaru - Miranda, Anggia Rizqi; Wardhana, Ali (PPJP ULM, 2023)
This study aims to determine the income of street vendors, namely income before the COVID-19 pandemic and income during the COVID-19 pandemic on Car Free Day Banjarbaru City. This study uses a quantitative approach with a descriptive method, which was conducted in January-February 2022. The income analysis method was used with the formula with 53 street vendors as respondents. The results of this study indicate that street vendors' income during the COVID-19 pandemic has decreased, with an average income of Rp. 645.962 with a maximum income of Rp. 2.230.000 merchandise and services traders are street vendors who experienced a substantial decline.